3D printing in situ gelification of κ-carrageenan solutions: Effect of printing variables on the rheological response. (February 2019) - Diañez, I.; Gallegos, C.; Brito-de la Fuente, E.; Martínez, I.; Valencia, C.; Sánchez, M.C.; Diaz, M.J.; Franco, J.M.
Abstract: This work reports a successful 3D printing-based in situ temperature-induced gelification procedure of κ-carrageenan aqueous dispersions. 3D printer was modified to handle low viscosity fluid feeding and more efficiently distribute ambient air at room temperature causing forced convection to accelerate the cooling of the printed layer. Thus, obtained gel samples, containing 30 mg/g κ-carrageenan in water, showed self-sustaining capability and a rheological response comparable with a reference conventionally prepared gel. Moreover, the effect of main printing variables, such as temperature of the hotend, printing speed and layer height, on the linear viscoelastic response of the gels was analysed by application of the response surface methodology (RSM). In general, gel strength linearly increases by decreasing printing speed and layer height whereas not noticeable improvement in gel strength was achieved by applying hotend temperatures above 80–85 °C. Based on the results obtained from this analysis, an optimisation method is proposed to minimise the temperature and time needed to 3D print a gel with pre-set rheological properties. Overall, this study demonstrates that it is possible to generate in situ 3D printed gel materials with potential uses in food and pharmaco-nutrition, without the aid of reactive additives or initiators, and using a facile protocol. Graphical abstract: Image 1 Highlights: RepRap 3D printing technology as quick, versatile and efficient tool to induce in situ gelation of κ-carrageenan solutions. Hotend temperature, printing speed and layer height influence viscoelastic response of carrageenan gels. High temperatures in combination with low speeds and layer heights result in more enhanced gel strength. Optimization of time-temperature relationship in the printing process for obtaining a given rheological response.